2013
DOI: 10.1590/s0101-20612013000100007
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and mineral and protein content of honey samples from Ceará state, Northeastern Brazil

Abstract: ResumoEste trabalho avaliou propriedades físico-químicas, teores de proteína e minerais em méis do Ceará, um dos principais exportadores do País. Também foi analisada a importância nutricional com relação aos minerais detectados. As propriedades físico-químicas foram determinadas pelos métodos da AOAC e CAC, o conteúdo de proteína pelo método de Bradford e os minerais por espectrometria de absorção atômica. Todas as análises foram feitas em triplicata. Os níveis dos macrominerais sódio (Na), potássio (K), cálc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
2
1
1
Order By: Relevance
“…The mean concentration of K (885.74 mg/kg) and Ca (113.84 mg/kg) in our honey samples was higher than those reported for honeys from Portugal (Silva, Sousa, & Taveira, 2017), Saudi Arabia (Alqarni et al, 2016), Morocco (Chakir et al, 2016) and lower than those reported for honeys from Malaysia (Moniruzzaman, Chowdhury, Rahman, Sulaiman, & Gan, 2014). The mean level of Fe (8.30 mg/kg), Zn (5.92 mg/kg), Mn (5.77 mg/kg) and Cu (1.18 mg/kg) was very high compared to those reported for honeys from Portugal (Silva et al, 2017), Italy (Di Bella et al, 2015), Brazil (Liberato et al, 2013) and much lower compared to those reported for honeys from Malaysia (Moniruzzaman et al, 2014). Moreover, Alqarni et al (2016) have reported a highly iron content in comparison to honey samples investigated in the present study.…”
Section: Mineral Compositioncontrasting
confidence: 58%
“…The mean concentration of K (885.74 mg/kg) and Ca (113.84 mg/kg) in our honey samples was higher than those reported for honeys from Portugal (Silva, Sousa, & Taveira, 2017), Saudi Arabia (Alqarni et al, 2016), Morocco (Chakir et al, 2016) and lower than those reported for honeys from Malaysia (Moniruzzaman, Chowdhury, Rahman, Sulaiman, & Gan, 2014). The mean level of Fe (8.30 mg/kg), Zn (5.92 mg/kg), Mn (5.77 mg/kg) and Cu (1.18 mg/kg) was very high compared to those reported for honeys from Portugal (Silva et al, 2017), Italy (Di Bella et al, 2015), Brazil (Liberato et al, 2013) and much lower compared to those reported for honeys from Malaysia (Moniruzzaman et al, 2014). Moreover, Alqarni et al (2016) have reported a highly iron content in comparison to honey samples investigated in the present study.…”
Section: Mineral Compositioncontrasting
confidence: 58%
“…Segundo Silva et al (2013) e Biluca et al (2014), o mel de ASF vem ganhando uma maior visibilidade devido às suas propriedades cicatrizantes, anti-sépticas, antimicrobiana, anticancerígeno, antiinflamatória, além do seu sabor, aroma e textura.…”
Section: Melunclassified
“…Estimation of total protein and carbohydrate Total amount of protein in honey was determined using Bradford assay against BSA (Bovine Serum Albumin) as a standard (Liberato et al, 2013). Total amount of carbohydrate present in honey samples were determined by anthrone method and dextrose was used as standard (Agbagwa et al, 2011).…”
Section: Water and Total Solidmentioning
confidence: 99%